Roots and fates of congenital insensitivity to pain and anhidrosis: a human phenotype - R. K., Rosheni; K. S., Surabhi; S. H., Fiza; D. R., Thanushree; George, Robin (International Journal of Research in Medical Sciences, 2024)
Congenital insensitivity to pain is a rare neurological disorder characterized by the inability to perceive physical pain. Individuals with CIP lack the typical nociceptive responses to harmful stimuli, which poses significant challenges to their safety and well-being. This condition is often caused by genetic mutations affecting the nervous system’s ability to transmit pain signals. Despite the apparent advantage of not experiencing pain, CIP presents severe risks as affected individuals may unknowingly sustain injuries or develop medical complications without timely intervention. The absence of pain perception hinders the learning of protective behaviour and responses to potentially harmful situations, making daily activities fraught with danger. Understanding the genetic basis of CIP has provided valuable insights into pain perception and the functioning of nociceptive pathways. While this knowledge may pave the way for potential therapeutic interventions, managing CIP remains a complex task. This article provides an overview of CIPA, its genetic basis, clinical manifestations, complications, treatment and the challenges associated with managing this complex condition. A multidisciplinary approach involving genetic counselling, pain management, and specialized care is crucial to support individuals with CIPA and improve their overall well-being.